PRACTICE BEYOND INSTRUCTION: EXPLORING PRACTICE STRATEGIES IN PRIMARY SCHOOL DRUM LEARNING - Sembiring, Piter; Latifah, Diah; Gunara, Sandie (Jurnal Ilmiah Didaktika, 2026)
This study addresses the limited attention given to independent practice in primary music education by examining how young students structure drum practice beyond direct instruction in a non-formal setting. A qualitative design was employed involving four students aged seven to nine, using participant observation, semi-structured interviews, and document analysis during thirty-minute sessions. Inductive thematic analysis revealed that students consistently initiated practice by revisiting previously learned 4/4 grooves, using prior material as a structural anchor. Despite tempo instability and coordination challenges between the hi-hat and bass drum, students maintained rhythmic coherence while negotiating motor demands. Problem-solving was predominantly global, relying on whole-pattern repetition rather than segmentation. Practice organization emerged implicitly, progressing from hi-hat stabilization toward full groove integration. These findings highlight early-stage self-structured practice behaviors and extend understanding of independent practice in drum learning. However, the small sample and single-context design limit generalizability. Future research should involve larger samples and longitudinal approaches to examine developmental progression in practice strategies.